Dexmedetomidine for the prevention of postoperative delirium in patients undergoing cardiac surgery: a systematic review and meta-analysis with trial sequential analysis - Yiyang Zhong; Zhizhen Ren; Jie Gao; Xingjian He; Qian Li (BMC Anesthesiology)
Abstract Background The efficacy of dexmedetomidine in preventing postoperative delirium (POD) following cardiac surgery remains controversial. This systematic review aimed to evaluate whether dexmedetomidine could prevent POD in patients undergoing cardiac surgery. Methods PubMed, CENTRAL, and Embase were searched up to 1 November 2024. Randomized controlled trials (RCTs) concerning dexmedetomidine for preventing POD in patients undergoing cardiac surgery were included. The primary outcome was the incidence of POD, and the secondary outcome was the incidence of postoperative atrial fibrillation (POAF). The analyses were performed using RevMan 5.3 and R 4.4.2 to calculate risk ratio (RR) with 95% confidence interval (CI). Trial sequential analysis (TSA) was conducted using TSA 0.9.5.10 Beta. Results Thirty-two studies with 6046 participants were included. Dexmedetomidine notably reduced the incidence of POD (RR = 0.67, 95% CI 0.59–0.76, P < 0.00001), with sufficient evidence and conclusive result from TSA. Dexmedetomidine was more effective in preventing POD compared with both positive control (RR = 0.47, 95% CI 0.38–0.59, P < 0.00001) and placebo control (RR = 0.83, 95% CI 0.70–0.98, P = 0.02). It reduced the incidence of POD not only in elderly patients (RR = 0.66, 95% CI 0.54–0.81, P < 0.0001) but also in normal age patients (RR = 0.68, 95% CI 0.57–0.80, P < 0.00001). Moreover, dexmedetomidine decreased the incidence of POAF (RR = 0.82, 95% CI 0.74–0.92, P = 0.0005). Conclusions Dexmedetomidine could reduce the incidence of POD in patients undergoing cardiac surgery and was associated with a decreased incidence of POAF. The findings should be interpreted with caution because of the low to moderate quality of evidence. Further trials are still needed to explore the optimal regimen of dexmedetomidine. Registration number: INPLASY2024110008.